2020
DOI: 10.1177/2333794x20931613
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice in Management of Childhood Fever Among Saudi Parents

Abstract: Fever is considered as a frequent symptom in childhood and is the cause of almost 65% to 70% of pediatric visits. Saudi Arabia has about 10% of child population (under 4 years of age), imposing a high burden of childhood illnesses including fever. A total of 1700 questionnaires were distributed to Saudi parents with children visiting pediatric clinic. Most of the participants were mothers (77.4%). A temperature of 38.0 °C was defined fever by 42% of participants. The majority of parents (80%) believed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
47
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(62 citation statements)
references
References 20 publications
(26 reference statements)
10
47
5
Order By: Relevance
“…There was a highly significant relationship between the correct body temperature considered as fever and mothers' level of education (p<0.01) [27]. Furthermore, Hussain et al [28], revealed that relationship and employment status of parents were found to be significantly associated with knowledge scores of parents for childhood fever. However, for attitude score, only age and number of children in the family found significant association, whereas for practice score, relationship, age, education level, and number of children in the family had significant association [28].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…There was a highly significant relationship between the correct body temperature considered as fever and mothers' level of education (p<0.01) [27]. Furthermore, Hussain et al [28], revealed that relationship and employment status of parents were found to be significantly associated with knowledge scores of parents for childhood fever. However, for attitude score, only age and number of children in the family found significant association, whereas for practice score, relationship, age, education level, and number of children in the family had significant association [28].…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, Hussain et al [28], revealed that relationship and employment status of parents were found to be significantly associated with knowledge scores of parents for childhood fever. However, for attitude score, only age and number of children in the family found significant association, whereas for practice score, relationship, age, education level, and number of children in the family had significant association [28]. These variables were further entered into the multivariate analysis to find the independent correlates of knowledge, behavior, and management practices for fever.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey questionnaire was developed based on previous studies to assess the knowledge, attitude, and practice of parents towards fever in children and its management (KAP) [ 17 , 18 , 20 ]. The KAP survey contained questions about the methods utilized for measuring body temperature, frequency of checking the temperature, attitude towards the complications of fever, methods to select the appropriate drug or doses administered, attitude towards alternating drugs, and practices in obtaining and using antibiotic drugs.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, another study by Hussain et al indicated many misconceptions regarding fever among the majority of parents. In addition to this, Saudi parents have demonstrated undue fear of consequent body damage from fever and also believe that antibiotics can reduce high temperature [ 18 ]. One of the ultimate goals of any local healthcare system is to provide appropriate care for children and enough educational knowledge for their parents, in the same manner as international and other healthcare systems, about the most common illnesses, such as fever.…”
Section: Introductionmentioning
confidence: 99%